Blast Exposure Leads to Accelerated Cellular Senescence in the Rat Brain - Arun, Peethambaran; Rossetti, Franco; Wilder, Donna M.; Sajja, Sujith; Van Albert, Stephen A.; Wang, Ying; Gist, Irene D.; Long, Joseph B. (Frontiers in Neurology, 2020)
Blast-induced traumatic brain injury (bTBI) is one of the major causes of persistent disabilities in Service Members, and a history of bTBI has been identified as a primary risk factor for developing age-associated neurodegenerative diseases. Clinical observations of several military blast casualties have revealed a rapid age-related loss of white matter integrity in the brain. In the present study, we have tested the effect of single and tightly coupled repeated blasts on cellular senescence in the rat brain. Isoflurane-anesthetized rats were exposed to either a single or 2 closely coupled blasts in an advanced blast simulator. Rats were euthanized and brains were collected at 24 hr, 1 month and 1 year post-blast to determine senescence-associated-β-galactosidase (SA-β-gal) activity in the cells using senescence marker stain. Single and repeated blast exposures resulted in significantly increased senescence marker staining in several neuroanatomical structures, including cortex, auditory cortex, dorsal lateral thalamic nucleus, geniculate nucleus, superior colliculus, ventral thalamic nucleus and hippocampus. In general, the increases in SA-β-gal activity were more pronounced at 1 month than at 24 hr or 1 year post-blast and were also greater after repeated than single blast exposures. Real-time quantitative RT-PCR analysis revealed decreased levels of mRNA for senescence marker protein-30 (SMP-30) and increased mRNA levels for p21 (cyclin dependent kinase inhibitor 1A, CDKN1A), two other related protein markers of cellular senescence. The increased senescence observed in some of these affected brain structures may be implicated in several long-term sequelae after exposure to blast, including memory disruptions and impairments in movement, auditory and ocular functions.